2007
DOI: 10.1093/pcp/pcm149
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D Signaling Regulates Microtubule Organization in the Fucoid Alga Silvetia compressa

Abstract: Recent studies in higher plants or animals have shown that phospholipase D (PLD) signaling regulates many aspects of development, including organization of microtubules (MTs), actin and the endomembrane system. PLD hydrolyzes structural phospholipids to form the second messenger phosphatidic acid (PA). To begin to understand the signaling pathways and molecules that regulate cytoskeletal and endomembrane arrays during early development in the brown alga, Silvetia compressa, we altered PLD activity by applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…We showed that genetic and pharmacological inhibition of PA generation results in microtubule depolymerization, which is consistent with results in tobacco cells (Dhonukshe et al, 2003) and algae (Peters et al, 2007). In leek (Allium porrum) leaves, 1-butanol converts microtubules from the transverse to longitudinal orientation, presumably by promoting microtubule detachment from the membrane (Sainsbury et al, 2008).…”
Section: Lipid Signaling Is Essential For Microtubule Organization Unsupporting
confidence: 87%
“…We showed that genetic and pharmacological inhibition of PA generation results in microtubule depolymerization, which is consistent with results in tobacco cells (Dhonukshe et al, 2003) and algae (Peters et al, 2007). In leek (Allium porrum) leaves, 1-butanol converts microtubules from the transverse to longitudinal orientation, presumably by promoting microtubule detachment from the membrane (Sainsbury et al, 2008).…”
Section: Lipid Signaling Is Essential For Microtubule Organization Unsupporting
confidence: 87%
“…13,14 We recently examined the roles of PLD signaling during early development of the brown alga S. compressa. 15 A fertilized egg normally orients its growth axis in accordance with directional light (photopolarization) and germinates and grows from the rhizoid pole of that axis. 16 The first division is asymmetric and is oriented transverse to the growth axis.…”
Section: Phospholipase D Signalingmentioning
confidence: 99%
“…17 We found that butanol treatments did not block photopolarization or germination, but cell division was inhibited. 15 This suggested that MTs, rather than actin or endomembranes, were the primary targets of drug treatment. This was a somewhat surprising finding since actin is often disrupted by 1-butanol application in plants and animals.…”
Section: Phospholipase D Signalingmentioning
confidence: 99%
See 2 more Smart Citations